Developing Skills for Youthful Leaders Module 4: Communicating With Others - Elizabeth B. Bolton; John R. Rutledge; Linda Bowman; Linda Barber (EDIS)
The objectives of this lesson are to show that the process of communication is more than words, to demonstrate that communication is important to relationships, and to recognize barriers to good communication and learn ways to overcome them. This document is FCS9091, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. EDIS publication date May 2006.